2017
DOI: 10.1155/2017/3059763
|View full text |Cite
|
Sign up to set email alerts
|

Danhong Huayu Koufuye Prevents Diabetic Retinopathy in Streptozotocin-Induced Diabetic Rats via Antioxidation and Anti-Inflammation

Abstract: Danhong Huayu Koufuye (DHK), a traditional Chinese prescription, is used to treat central retinal vein occlusion clinically. We previously reported that DHK prevented diabetic retinopathy (DR) in rats. Moreover, we found that it protected endothelial cells from hyperglycemia-induced apoptosis through antioxidation and anti-inflammation. Here, we investigated whether antioxidative and anti-inflammatory activities of DHK contributed to its therapeutic effect on DR in streptozotocin- (STZ-) induced diabetic rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…4C, E; all P <0.001, Normal vs DM). These results were consistent with the previous reports [20, 29, 30]. More importantly, α-MSH intravitreal administration significantly increased the thickness of all the retinal layers in diabetic retinas (Fig.…”
Section: Resultssupporting
confidence: 93%
“…4C, E; all P <0.001, Normal vs DM). These results were consistent with the previous reports [20, 29, 30]. More importantly, α-MSH intravitreal administration significantly increased the thickness of all the retinal layers in diabetic retinas (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Clinically, DHK is mainly used for treatment of blurred vision and sudden blindness caused by qi stagnation and blood stasis, as well as the absorption period of central retinal vein occlusion. As previous studies reported, DHK has antioxidant and anti‐inflammatory activities, and can effectively prevent deep vein thrombosis (Chen et al, ; Zhang et al, ; Zhang et al, ). However, the bioactive components of DHK are still not well understood, and current quality standards only stipulate the quantitative determination of protocatechualdehyde, which largely restricts the quality control and further development of DHK.…”
Section: Introductionmentioning
confidence: 78%
“…VEGF is a proangiogenic factor regulator that damages the blood-retina barrier (BRB) by several mechanisms, leading to increased vascular permeability and the development of retinal edema. An imbalance between proangiogenic mediators and ischemia result in the growth of abnormal leaky blood vessels, eventually leading to retinal neovascularization [ 3 , 38 ].…”
Section: Discussionmentioning
confidence: 99%